Second Five Year (Draft) Plan Himachal Pradesh Government - Planning Commission (Planning Commission, 1953)
During the 2nd Five Year Plan period development in the various towns of the District is to be implemented to give them an economic outlook. The District Itself is backward and poor and as such the finances of the Local Bodies of the towns are not adequate to contribute towards the cost required for the implementation of the various development activities. In the District there are one Municipality at Solan, two Small Town Committees at Rampur and Theog and two Notified Area Committees at Arkit and Narkanda.
Himachal Pradesh Government Department of Development and Planning
Himachal Pradesh Government Department of Development and Planning